Identification of Textured Tactile Pictures in Visually Impaired and Blindfolded Sighted Children - Vinter, Annie; Orlandi, Oriana; Morgan, Pascal (Frontiers in Psychology, 2020)
A high level of variability in the capacity of visually impaired children to accurately identify tactile images is reported in the literature, with on average rather low percentages of correct naming responses. However most of these studies used raised-line drawings as stimuli to be explored and named. The present experiment investigated whether blind children of 3 to 8 years of age would demonstrate a satisfactory ability to name the elements making up tactile images when tested in an experimental setting similar to their natural reading conditions. Textured tactile images taken from genuine illustrated tactile books for young children were used, and the participants received information about the title of the book or listened the text that accompanied each picture before exploration, as it would occur in a natural reading setting. The results showed that their naming scores were indeed higher than previously reported at equivalent ages and did not differ from those of age-matched sighted children. These scores were positively impacted by haptic practice in blind children and correlated with the use of some specific exploratory procedures. The blind children benefited from information provided before exploration, as did their sighted counterparts. However, only in the former did the condition in which full information was provided influence the way the children organized their exploration. The haptic identification scores increased with age regardless of visual status, with the exploration times decreasing in the blind children, while the reverse trend was observed in the sighted children. These results are discussed at the light of the image-mediation model of haptics, suggesting that during the age period considered in the present experiment, blind children would progressively learn to process haptic information directly, thus leading to a decrease of exploration times, while sighted children would learn to translate haptic information into a visual image used to retrieve semantic information, involving an increase of their exploration times.